مواقع الشبكات الاجتماعية قراءة في سوسيولوجيا الاستخدام - مهدي, سامية (University of Eloued جامعة الوادي, 2016)
يهدف هذا المقال لإعادة التفكير في التراث النظري المتوافر في حقل علوم الإعلام والاتصال، الذي يهتم بدراسة " مواقع الشبكات الاجتماعية". والذي نقر بعجزه ،إن صح التعبير، على تقديم إطار تحليلي لفهم سوسيولوجيا استخدام هذه المواقع باعتبارها الوسيط الأكثر استخداما وشعبية ، لذلك نحاول طرح مقاربة " سوسيولوجيا الاستخدام" كإطار نظري تحليلي ، يرى أن فهم الممارسات والأنماط الاتصالية الجديدة يتم في إطار العلاقة التفاعلية بين الإنسان والآلة. انطلاقا من فكرة " البناء الاجتماعي للاستخدام" ، التي تنطلق من مسلمة هذا التيار، والتي تقر أن فعل الاستخدام يقوم بين وساطة التقني والاجتماعي. وتقترح مقترب " التمثلات الاجتماعية" كمدخل لفهم عملية هذا البناء tract : This research aims to rethink in the available theorem heritage in the information and communication sciences field, interesting in the "social networking sites". This heritage is unable to provide us with an analytical firm to understand usage sociology of the social networking sites. Therefore, we try to represent an approach 'usage sociology" as a theoretic analytical firm showing that understanding new practices and communicational types is carried out by the relation between human and machine considering in the first time the social construction of usage's idea that discloses that the action of usage occurs between the technical and social mediation and suggests the "approach of social representations" as an introduction to understand the construction process
Social networking sites Study about usage sociology
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: مواقع الشبكات الاجتماعية، سوسيولوجيا الاستخدام،. البناء الاجتماعي للاستخدام ، مقاربة التمثلات; Social networking sites, usage sociology, social construction of usage, representations' approach